An evaluation of sonographic parameters of fetal growth, maternal glycemia and pregnancy outcome of gestational diabetes mellitus in a Sri Lankan tertiary care unit - Prathapan, R.; Dodampahala, S.H.; Wijeyaratne, C.N.; Jayawardana, A.; Prathapan, S.; Wijerathne, S.; Wijesingha, E.; Abrew, K.A.G; Wickmmasinghe, S.W.A.D.; Priyanga, L.M; Karunarathne, D.A.S. (My University, 2007)
OBJECTIVES To assess the relationship of maternal glycaemic status and fetal growth of gestational diabetic pregnancies (GDM) in Sri Lankan women attending a tertiary specialized unit. OUTCOME MEASURES To correlate maternal glycaemia with 1. ultrasound characteristics of fetal growth 2. cord blood HbAlc percentage 3. pregnancy outcome- birth weight; neonatal morbidity and mortality. METHOD Consecutive consenting women aged 18-35 years, at antenatal booking were recruited. Ultrasound scan confirmed dates and a singleton pregnancy. All were screened and pre-existing diabetes were excluded. GDM was diagnosed by a 2 hour 75g OGTT at 24-26 weeks. All GDM and a cohort were followed up till delivery. Based on blood sugar profile the insulin doses were adjusted 2weekly to target pre-meal values to 90mg/dl and post meal value less than 130mg/dl. EXCLUSION CRITERIA Multiple pregnancies, pre existing medical conditions including diabetes, previous fetal growth restriction and poor obstetric history. The abnormal glucose tolerance test group received standard care by a multi-disciplinary team. Maternal glycaemia was assessed with 6 point BSS and fetal growth assessed by serial ultrasound at 28-29 and 34-35 weeks. Cord blood HbAlc percent and birth weight were recorded. RESULTS 114 mothers of 198 consenting women had completed the study. Mean pre-meal and post-meal blood sugar values at 28 weeks were 153.2mg/dl + 30.8, 181.4 mg/dl + 30.0 in GDM pregnancies vs 88.8 mg/dl + 12.4,111.8 mg/dl + 15.5 in non diabetic pregnancies.(p=0.001). Corresponding values at 34 weeks were 131.6 mg/dl + 30.3, 160.3 mg/dl + 30.5 and 100.7 mg/dl + 6.2, 116.01 mg/dl + 10.5.(p = 0.001) Statistically significant difference was found in mean fetal abdominal circumference and estimated fetal weight (Hadlock) in the two groups at 28 and 34 weeks. Mean HbAlc percentage in cord blood was 1.84 + 0.30 in GDM and 1.80 + 0.31 in the non diabetics. (p = 0.43). The mean birth weight in the GDM was 3.051kg + 0.59 and in non diabetics was 2.977kg + 0.35 (p=0.45).There were no neonatal deaths reported in both groups. A single fetal adverse outcome (brachial plexus palsy) occurred in the non diabetic neonate. CONCLUSION This study confirms that fetal weight based on USS biometry at 28 weeks and 34 weeks is a good reflector of maternal glycaemic status. The Maternal glycaemic targets achieved in a Sri lankan setting are satisfactory
Keywords: Sonographic Parameters; Fetal Growth; Maternal Glycemia; Pregnancy Out Come; Gestational Diabetes Mellitus; Tertiary Care; Sri Lanka